2021
DOI: 10.3847/2041-8213/abe874
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Spectrum of Protonated C70

Abstract: With the detection of C 60 , C 70 , and + C 60 in the interstellar medium, fullerenes are currently the largest molecules identified in space. The relatively high proton affinities of C 60 and C 70 support the hypothesis that protonated fullerenes may also be abundant in the interstellar matter. Here, we present the first experimental vibrational spectrum of C 70 H + , recorded in the gas phase. The attachment of a proton to C 70 causes a drastic symmetry lowering, which results in a rich vibrational spectrum.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…In addition, C 60 was detected earlier [19,20] in various nebulae (see [21] and references therein) by emission of infrared radiation. Recently, laboratory infrared spectra of C + 60 , C 60 H + , and C 70 H + were also reported and compared with observations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, C 60 was detected earlier [19,20] in various nebulae (see [21] and references therein) by emission of infrared radiation. Recently, laboratory infrared spectra of C + 60 , C 60 H + , and C 70 H + were also reported and compared with observations [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 48 We noticed earlier that this feature resembles the spectral characteristics of protonated C 60 and C 70 . 19 , 20 We suggested that a mixture of these protonated fullerenes, perhaps together with radical cation fullerenes, may give rise to this emission feature. Here, we add the newly recorded spectra of the oxidized fullerene analogues to the comparison.…”
Section: Resultsmentioning
confidence: 88%
“…The APCI source is particularly suitable for studying apolar substances such as PAHs 40 and fullerenes. 19 , 20 The DIP inlet replaces the spray nebulizer on the standard Bruker APCI ion source. The solid sample is placed on the tip of a single-use glass tube of the DIP, where it is heated and sublimates into the APCI source chamber.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations